Küresel lojistik performans endeksi ve Türkiye’nin son 10 yıllık lojistik performansının analizi - Yapraklı, Tevfik Şükrü; Ünalan, Musa (My University, 2016)
Lojistik, üretim ve tüketim noktaları arasındaki malzeme ve bilgi akışının yönetilmesi sürecini kapsar. Dünya çapında ticaret ve taşımacılıkta serbestleşme eğiliminin hızlanması, lojistik sektörünün stratejik bir sektör olarak görülmesini sağlamıştır. Bu çalışmada, 2007 yılı ve sonrasında 2010, 2012, 2014, 2016 yıllarında, Dünya Bankası Uluslararası Ticaret Birimi tarafından yayınlanan Lojistik Performans Endeksi raporları esas alınarak; ülkeler bazında lojistiğin küresel boyuttaki durumu ile Türkiye’nin lojistik bakımından uluslararası piyasadaki konumu incelenmiştir. Ülkelerin endeks içerisindeki sıralamaları belirlenirken, altı temel bileşen dikkate alınmıştır. Bu bileşenler; gümrükler dahil sınır denetim kuruluşlarının gerçekleştirdiği gümrükleme işlemlerinin verimliliği, ticaret ve taşımacılık ile bağlantılı altyapının kalitesi, rekabetçi fiyatlarla sevkiyat düzenlenmesindeki kolaylık, lojistik hizmetlerde yetkinlik ve kalite, sevkiyatların izlenebilirliği ile sevkiyatlarının planlanan zamanda varış yerine ulaşmasındaki zamanlamadır. Çalışmanın sonucunda, Türkiye’nin son on yılda lojistik performans açısından hem genel hem de alt bileşenler bazında ilerleme sağladığı fakat dünya sıralamasındaki yeri bakımından ciddi bir değişikliğin olmadığı görülmüştür. 2007 yılında dünya ekonomisindeki sıralaması 34. sıra olurken 2016’da bu sıralama değişmemiştir. Hem endeks skoru bakımından hem de sıralama bakımından en iyi dönemin 2012 olduğu görülmüştür. En yüksek iyileştirmenin olduğu alt bileşen altyapı olurken, en düşük iyileştirme ise lojistik kalite ve yetkinlik olmuştur. Logistics contains the process of material and information flow management between production and consumption. Logistics sector as a strategic sector because of accelerating of liberalization trend on trade and transportation in the worldwide. In this study, the situation of global logistics in terms of countries and the position of Turkey in international market with regard to logistics have been examined on the basis of Logistics Performance Index reports which published by the World Bank International Trade Department in 2007, 2010, 2012, 2014, 2016. There are six components to determine the ranking of countries according to Logistics Performance Index. These are the efficiency of custom and border clearance, the quality of trade and transport infrastructure, the ease of arranging competitively price shipments, the competence of quality of logistics, the ability to track and trace consignments, and the frequency which shipments reach consignees within scheduled. As a result of the study concluded that while Turkey’s general Logistics Performance Index and components increased in terms of score, the ranking of Turkey in the worldwide did not change significantly from 2007 to 2016. The ranking of Turkey is 32 in both 2007 and 2016. The best period of Turkey in order to ranking and logistics performance is the year of 2012. A component which is the highest improvement in six components is the infrastructure, while a component which is the lowest improvement in six components is the logistics quality and competence for Turkey.

Logistics contains the process of material and information flow management between production and consumption. Logistics sector as a strategic sector because of accelerating of liberalization trend on trade and transportation in the worldwide. In this study, the situation of global logistics in terms of countries and the position of Turkey in international market with regard to logistics have been examined on the basis of Logistics Performance Index reports which published by the World Bank International Trade Department in 2007, 2010, 2012, 2014, 2016. There are six components to determine the ranking of countries according to Logistics Performance Index. These are the efficiency of custom and border clearance, the quality of trade and transport infrastructure, the ease of arranging competitively price shipments, the competence of quality of logistics, the ability to track and trace consignments, and the frequency which shipments reach consignees within scheduled. As a result of the study concluded that while Turkey’s general Logistics Performance Index and components increased in terms of score, the ranking of Turkey in the worldwide did not change significantly from 2007 to 2016. The ranking of Turkey is 32 in both 2007 and 2016. The best period of Turkey in order to ranking and logistics performance is the year of 2012. A component which is the highest improvement in six components is the infrastructure, while a component which is the lowest improvement in six components is the logistics quality and competence for Turkey
The global logistics performance index and analysis of the last ten years logistics performance of Turkey
Bildiri - Yayımlanmış
Keywords: Türkiye; Lojistik sektörü; Lojistik performans endeksi; Logistics sector; Logictics performance index; Turkey